Ultraprocessed food consumption and dietary nutrient profiles associated with obesity: A multicountry study of children and adolescents (2022)
ABSTRACT: This study assessed associations between ultraprocessed food consumption and die-tary nutrient profile linked to obesity in children and adolescents in Argentina,Australia, Brazil, Chile, Colombia, Mexico, the United Kingdom, and the United Statesusing nationally representative data collected between 2004 and 2014. Linear regres-sion models were used to evaluate associations between dietary share ofultraprocessed foods (country and age group-specific quintiles and a 10% shareincrease) and the energy density of diets and their content of free sugars and fiber.Ultraprocessed foods, defined by the NOVA system, ranged from 18% of total energyintake among preschool children in Colombia to 68% among adolescents in theUnited Kingdom. In almost all countries and age groups, increases in the dietary shareof ultraprocessed foods were associated with increases in energy density and freesugars and decreases in fiber, suggesting that ultraprocessed food consumption is apotential determinant of obesity in children and adolescents. Effective global policy action to address growing ultraprocessed food consumption and childhood obesity isurgently needed.KEYWORDSchildhood obesity, nutrient profile, ultraprocessed foods.